Field evaluation of a Mycoplasma bovis bacterin in young dairy calves - Maunsell, Fiona P. (Vaccine, 2009)
Mycoplasma bovis is an important cause of pneumonia, otitis media and arthritis in young dairy calves, and there is a critical need for improved preventative strategies for this pathogen. We conducted a randomized, placebo-controlled, double-blinded field trial to determine the efficacy of a commercial M. bovis vaccine for the prevention of M. bovis-associated disease in calves. Calves (n = 373) on 3 Florida dairies with a history of M. bovis infection received an M. bovis bacterin or a placebo, administered subcutaneously at 3, 14 and 35 days of age. One of the herds did not experience M. bovis-associated disease; for calves in the remaining 2 herds, the incidence risk for respiratory disease, otitis media and arthritis from 3 to 90 days of age was 0.64, 0.28 and 0.02, respectively. Vaccination had no effect on the age at first treatment for M. bovis-associated disease, incidence of respiratory disease, mortality, weight gain, or nasal colonization with M. bovis in the first 90 days of life. In one herd, vaccination was associated with an increased risk of otitis media. There was no association between M. bovis-specific serum antibody titers and morbidity in vaccinated calves. Under the field conditions in this study, this vaccine was not efficacious for the prevention of M. bovis-associated disease in young dairy calves.